Impact Analysis of VVIP and VIP Flight Activities on the Smoothness of Commercial Flights at Bali's I Gusti Ngurah Rai International Airport - Dewa Wahyu Satria Pemayun; Andi Syaputra (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
I Gusti Ngurah Rai International Airport is an airport for several purposes, from the needs of VVIP and VIP guests to commercial needs. Some of these types of flights certainly have differences, VVIP and VIP flights are a priority at the airport. Disruption to the smooth operation of commercial flights, which was partly caused by VVIP and VIP guests coming and going to the island of Bali through I Gusti Ngurah Rai airport. This study uses inductive/qualitative data analysis. The method used for this research is the method of documentation, observation, and interviews with Airport Operation Landside and Terminal officers. This research was conducted for 2 months, starting from 01 November 2022 to 31 December 2022 at the Airport Operation Landside and Terminal unit. The results of the research conducted can be concluded that VVIP (Very Very Important Person) and VIP (Very Important Person) flight activities at I Gusti Ngurah Rai International Airport in Bali greatly affect commercial flight activities, causing commercial flights to be temporarily stopped or flight schedules changed. , and the airport has prepared for handling in such a way as to reduce the impact caused by VVIP flights on commercial flights.